The Implementation of Make A Match Type Cooperative Learning Model to Improve the Mathematical Connection Ability - Maulidawati, Maulidawati; Muhammad, Iryana; Rohantizani, Rohantizani; Mursalin, Mursalin (International Journal for Educational and Vocational Studies, 2020)
Mathematics is a discipline that is taught at every level of education in Indonesia. Mathematics are interrelated with each other, and cannot be separated from other disciplines and problems in everyday life. Process standards that students use in learning mathematics include problem solving, reasoning and proof, connection, communication, and representation. This study aims to determine the mathematical connection ability of students who are taught through the make a match cooperative learning model better than the students' mathematical connection ability through the scientific learning model on the line and row material in class XI SMAN 1 Pintu Rime Gayo. This research is a quasi-experimental study using the pretest-posttest group design. The samples taken were class XI MIA 2 as the experimental class and XI MIA 1 as the control class. Retrieval of data in research using tests. The data collected from the test results were analyzed using SPSS version 18 to find normality using the Shapiro-Wilk test and to test the hypothesis using the Mann-Whitney-Test. Based on the results of data analysis, it shows that the N-gain average score of students who apply the make a match cooperative learning model is 0.71 (high category), higher than students who use scientific learning of 0.36 (moderate category). From the results of the Mann-Whitney-Test above, the Asymp value is obtained. Sig (1-tailed) is 0.0005 <Î± 0.05. This shows that the increase in students' mathematical connection ability through cooperative learning type make a match is significantly better than students who get scientific learning.